Are bacteria claustrophobic? The problem of micrometric spatial confinement for the culturing of micro-organisms. Issue 21 (30th March 2021) - Molinaro, Céline; Da Cunha, Violette; Gorlas, Aurore; Iv, François; Gallais, Laurent; Catchpole, Ryan; Forterre, Patrick; Baffou, Guillaume
Abstract : Observation of bacterial growth inhibition under spatial confinement, experimentally (left) and numerically (right). Abstract : Culturing cells confined in microscale geometries has been reported in many studies this last decade, in particular following the development of microfluidic-based applications and lab-on-a-chip devices. Such studies usually examine growth of Escherichia coli. In this article, we show that E. coli may be a poor model and that spatial confinement can severely prevent the growth of many micro-organisms. By studying different bacteria and confinement geometries, we determine that the growth inhibition observed for some bacteria results from fast dioxygen depletion, inherent to spatial confinement, and not to any depletion of nutriments. This article unravels the physical origin of confinement problems in cell culture, highlighting the importance of oxygen depletion, and paves the way for the effective culturing of bacteria in confined geometries by demonstrating enhanced cell growth in confined geometries in the proximity of air bubbles.